MODEL PEMBELAJARAN KONTEKSTUAL RELATING, EXPERIENCING, APPLYING, COOPERATING, AND TRANSFERRING (REACT) DENGAN SIMULASI VIRTUAL DALAM PEMBELAJARAN FISIKA DI SMA (MATERI MOMENTUM, IMPULS DAN TUMBUKAN KELAS X SMAN 2 JEMBER) - Firdha Choirun Nisa; Albertus Djoko Lesmono; Rayendra Wahyu Bachtiar (FKIP Universitas Jember, 2018)
AbstractThe purpose of this research were to examine the effect of contextual learningmodel of Relating, Experiencing, Applying, Cooperating, and Transferring (REACT)with Virtual Simulation to critical thinking ability and student learning activity inSenior High School. The type of this research was experimental research using posttest only control group design. Population in this research was the tenth gradestudents of SMAN 2 Jember. The data were collected by observation, documentation,interview and test. The data were analyzed using Independent Sample T-Test withSPSS 24. The results showed that the average value of critical thinking ability ofexperimental class was 81,15 and control class was 69,91. In result of activity valueof experiment class was 86,943 and control class was 79,934. This study can beconcluded REACT learning model with virtual simulation have an effect onsignificance to critical thinking ability and student activity in physics learning insenior high school.Keywords: Contextual learning model of REACT, virtual simulation, criticalthinking, student learning activity